2011
DOI: 10.1029/2011ja016690
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of EMIC wave-associated He+energization in the outer magnetosphere: Cluster/CODIF observations

Abstract: , the Composition and Distribution Function (CODIF) Analyzer on board Cluster observed 41 prolonged He + energization events, lasting for 1.10-4.97 h, on average, 3.18 ± 0.91 h. These He + heating events occurred predominantly at low/middle magnetic latitudes (MLAT = −4.3°-51.7°) in the afternoon sector in the outer magnetosphere (L = 7.9-14.6). During the events, the He + ions resonantly interacted with electromagnetic ion cyclotron (EMIC) waves and were perpendicularly energized to energies up to 1 keV. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 69 publications
(134 reference statements)
6
79
0
1
Order By: Relevance
“…Before the shock passage at 02:25 UT, the total density n pot was 10 cm −3 and the ESA electron density was 1 cm −3 (not shown). Therefore, the density of the cold population is 9 cm −3 , indicating that THEMIS A most probably observed a plasmaspheric plume (e.g., Goldstein et al, 2004;Zhang et al, 2011). The density increased to 30 cm −3 at 02:26 UT and 100 cm −3 at 02:29 UT.…”
Section: Spacecraft Observationsmentioning
confidence: 87%
“…Before the shock passage at 02:25 UT, the total density n pot was 10 cm −3 and the ESA electron density was 1 cm −3 (not shown). Therefore, the density of the cold population is 9 cm −3 , indicating that THEMIS A most probably observed a plasmaspheric plume (e.g., Goldstein et al, 2004;Zhang et al, 2011). The density increased to 30 cm −3 at 02:26 UT and 100 cm −3 at 02:29 UT.…”
Section: Spacecraft Observationsmentioning
confidence: 87%
“…Although EMIC waves have been intensively investigated [e.g, Kennel and Petschek, 1966;Young et al, 1981;Rauch and Roux, 1982;Roux et al, 1982;Anderson et al, 1996;Fraser and Nguyen, 2001;Halford et al, 2010;Pickett et al, 2010;Zhang et al, 2010Zhang et al, , 2011Min et al, 2012;Allen et al, 2013;Lin et al, 2014], plasma properties relevant to EMIC wave excitation have not been fully understood in the magnetosphere due to the wide spatial extent of EMIC wave generation and propagation. For example, Lin et al [2014] recently found that the correlation of positive A hp events, EMIC instability threshold (Σ h > S h ), and EMIC waves observed by the polar-orbiting Cluster spacecraft is low.…”
Section: Discussionmentioning
confidence: 99%
“…EMIC waves are preferentially generated in regions where hot anisotropic H + and cold dense ion populations spatially overlap [e.g., Jordanova et al, 2001;Pickett et al, 2010;Zhang et al, 2011]. In the terrestrial magnetosphere, these ion populations can commonly be found where the ring current overlaps the plasmasphere or plasmaspheric plumes [Gurgiolo et al, 2005;Thorne, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Between these two branches is a frequency stop band in which no Alfvénic fluctuations can grow [ Gomberoff and Neira , 1983; Kozyra et al , 1984]. This stop band is often observed in EMIC spectra from the outer magnetosphere [e.g., Young et al , 1981; Roux et al , 1982; Zhang et al , 2010, 2011]. Second, cool helium ions also permit the lower frequency branch to become unstable at wavelengths shorter than those which would be unstable in an electron‐proton plasma.…”
Section: Introductionmentioning
confidence: 99%